Dimensiones sintomáticas psicopatológicas por miedo al COVID-19 en Policías de la DINASED. Quito, 2021 - Yambay Moyano, Jessica Nataly (2022)
The objective of this research was to analyze the symptomatic psychopathological dimensions due to fear of COVID-19 in specialized police officers from DINASED. The methodology used was quantitative, bibliographic, and field approach; the design was non-experimental and cross-sectional, of descriptive and correlational level. The sample was 70 police officers aged 24 to 56 years old. The instruments applied were the SCL-90-R Symptom Inventory and the Scale of Fear of Coronavirus COVID-19 (FCV-19S), which were digitized through Google Forms. The relevant results point out that the police officers present somatizations (7% symptoms of clinical severity), anxiety (7% symptoms with moderate clinical significance), and phobic anxiety (10% of symptoms with moderate clinical significance and 6% of clinical severity). Regarding the fear levels, it determined that 13% of the policewomen have a low level of fear and 1% has a high level of fear of COVID-19. While in the policemen, 69% show a low level of fear, and 17% present a high level of fear of COVID-19. It concluded that there is a positive relationship (p <0.05) between psychopathological symptoms (somatization, anxiety, and phobic anxiety) and fear of COVID-19. It was verified that to more excellent the fear, the greater the presence of psychopathological symptoms.